Does the pre-operative value of serum CA15-3 correlate with survival in breast cancer? - Velaiutham, S.; Taib, N.A.; Ng, K.L.; Yoong, B.K.; Yip, C.H. (West Asia Organization for Cancer Prevention, 2008)
Estimation of CA15-3 at presentation of breast cancer is important as it is an independent prognostic indicator and may prompt the physician to investigate for metastases if elevated.